DARE Newsletter, Vol. 19, No. 2, Fall 2016 - DARE; Goebel, George; Schnebly, Julie (Dictionary of American Regional English, 2016)
Contents: "The News from DARE" by George Goebel; "DARE and Mental Floss" by Julie Schnebly; "Discount on Digital DARE"; "Want to Go Paperless?"; "In Memoriam: Donald Oresman"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States